Perception et autoportrait de l’interprète indigène en Afrique coloniale française - Mopoho, Raymond (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
African interpreters were hired to serve as intermediaries between Europeans and Africans, but they ended up establishing themselves as key parties in the mediation process, wielding as much power as both the colonial administrators and the traditional authorities. In so doing, they actively participated in the colonial enterprise, which involved dominating and exploiting native masses, promoting Eurocentrism, as well as fostering the rule of injustice and violence. Although in the African community the interpreter ’s status brought him privile ges and some respect, he was viewed with suspicion – and even contempt – by European colonial officers, who considered him as a threat to their own existence. Eventually, this indirect actor of the disintegration of African traditional societies could really identify neither with his fellow natives, for whom he was part of the colonial administration, nor with Europeans, who would rather keep him in a state of servitude. His personality reflected the contradictions of the new social order which he had helped to establish.